Lactancia materna y estado nutricional en niños y niñas menores de dos años de la Zona 7 del Ecuador - Espinosa Sarango, Yadira Lizbeth (2024)
Alterations in the nutritional status of children represent a major public health problem due to the consequences that occur in the short and long term. Inadequate nutrition is one of the main associated factors and a fundamental food during this stage is breast milk. That is why the objective of this work was to determine the influence of breastfeeding on the nutritional status of boys and girls under two years of age in Zone 7 of Ecuador. An analytical-quantitative, cross-sectional, non-experimental, retrospective and correlational study was carried out in a sample of 1063 boys and girls under two years of age. The information was obtained from the database of the “National Child Malnutrition Survey, period 2022-2023”, carried out by the National Institute of Statistics and Censuses of Ecuador. The findings show that 77.14% of boys and girls have a normal nutritional status; In addition, malnutrition due to deficiency and excess was observed; 15.9% presented malnutrition; 5.55%, overweight; and 1.41%, obesity. Regarding the start of breastfeeding, 59.32% had an early start; the prevalence of exclusive breastfeeding during the first six months is 30.89%; and, of continuous breastfeeding in boys and girls from 12 to 23 months of age, is 51.73%. 42.90% received mixed breastfeeding, of which 33.12% consumed formula milk, while 19.95% received cow's milk. The Pearson Chi-square test shows that there is no relationship between the variables; However, in infants from 0 to 5 months of age, exclusive breastfeeding seems to be a protective factor, given that children who receive mixed breastfeeding present greater malnutrition, overweight and obesity